A glimpse into the history of description of the antiphospholipid syndrome. (October 2020) - Nour-Eldine, Wared; Noureldine, Hussein A; Haydar, Batoul A; Eldine, Mariam Nour; Noureldine, Mohammad Hassan A; Uthman, Imad
Prior to 1983, several landmark reports prepared the stage for a detailed description of the Antiphospholipid (Hughes) syndrome (APS). Formerly depicted as lupus-like, APS exhibits a wide spectrum of symptoms that overlap with Sjogren's, Hashimoto, and other autoimmune diseases. In this review, we take a glimpse into the history of description of APS, discussing the events that led to its recognition as one of the most common autoimmune diseases and the enormous impact of that recognition in the rheumatology field.